Promoting health education through mobile apps: A quantitative analysis about the world’s best hospitals - Medina Aguerrebere, Pablo; Medina, Eva; Gonzalez Pacanowski, Toni (Revista Española de Comunicación en Salud, 2023)
Introduction: Promoting health education through different platforms (patient portals, social media, websites) has become a common practice in many countries. Recently, many hospitals have prioritized mobile apps as a health education tool. Objectives: This paper aims to analyze how hospitals should use mobile apps to promote health education efficiently and this way improve their relations with patients. Methodology: To answer this question, we carried out a literature review about health education, mobile apps, patients’ empowerment, and noncommunicable diseases; and then, we resorted to 38 indicators to analyze how the top 150 hospitals in the world manage these platforms to promote health education. Conclusion: We concluded that the three main criteria that hospitals should consider when using mobile apps for health education purposes are: 1) respecting patients’ needs in terms of information and emotional support; 2) evaluating health professionals’ and patients’ skills in mobile literacy; and 3) considering public health priorities.
Keywords: hospitals; health education; mobile apps; patients; noncommunicable diseases